Different expression of integrins by mononuclear phagocytes in peripheral blood and bronchoalveolar lavage fluid - Stríz, I; Pokorná, H; Zheng, L; Guzman, J; Costabel, U (Respiratory medicine, 1998)
Alveolar macrophages (AM) originate from blood monocytes and, during the maturation process, undergo functional and morphological changes which are also reflected in their phenotypic pattern. Among the macrophage membrane antigens, adhesion molecules of the integrin family are particularly important for effector functions and cell-cell interactions. The aim of this study was to analyse the membrane expression of selected integrins by AM recovered from bronchoalveolar lavage (BAL) as compared to their precursors, peripheral blood monocytes (PBM). The cells were stained using a sensitive immunoperoxidase assay with 10 different monoclonal antibodies. The data showed a higher expression by AM than PBM of all but one of the studied adhesion molecules. The only exception was CD11b (Mac-1, CR3) which showed a higher expression in PBM than in AM. Several molecules, for example, CD49d (VLA-4), CD51 (vitronectin receptor), and CD54 (intercellular adhesion molecule-1, ICAM-1) were found to be upregulated by AM in patients with a lymphocytic pattern of BAL. In contrast, the phenotype of PBM does not show any changes in these patients. In conclusion, we have demonstrated differences in the expression of integrins between AM and PBM which can be partially responsible for some of their functional differences.
Keywords: buněčná membrána; Antigens, CD; CD antigeny; neparametrická statistika; Humans; lidé středního věku; Integrins; Female; dospělí; Bronchoalveolar Lavage Fluid; separace buněk; lidé; plicní nemoci; Immunohistochemistry; imunohistochemie; Adult; ženské pohlaví; Male; Lung Diseases; Middle Aged; bronchoalveolární lavážní tekutina; integriny; Macrophages, Alveolar; Cell Separation; Statistics, Nonparametric; Monocytes; monocyty; Cell Membrane; mužské pohlaví; alveolární makrofágy